2020
DOI: 10.1038/s12276-020-00526-2
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of the 3D genome by the ATPase machine cohesin

Abstract: The spatial organization of the genome is critical for fundamental biological processes, including transcription, genome replication, and segregation. Chromatin is compacted and organized with defined patterns and proper dynamics during the cell cycle. Aided by direct visualization and indirect genome reconstruction tools, recent discoveries have advanced our understanding of how interphase chromatin is dynamically folded at the molecular level. Here, we review the current understanding of interphase genome or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 84 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…There are indications that TAD formation and phase separation are counteracting processes (Y. Kim & Yu, 2020), raising the question whether the loading of cohesin at Scc2/4-mediated DNA-condensates determines whether cohesin promotes loop extrusion or sister chromatid cohesion. As cohesin degradation in vivo leads to the loss of all DNA loops but not of the condensation-mediated compartmentalization of chromatin (Rao et al, 2017), it is likely that phase separation does not cause loop extrusion but both processes co-exist.…”
Section: Ideas and Speculationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that TAD formation and phase separation are counteracting processes (Y. Kim & Yu, 2020), raising the question whether the loading of cohesin at Scc2/4-mediated DNA-condensates determines whether cohesin promotes loop extrusion or sister chromatid cohesion. As cohesin degradation in vivo leads to the loss of all DNA loops but not of the condensation-mediated compartmentalization of chromatin (Rao et al, 2017), it is likely that phase separation does not cause loop extrusion but both processes co-exist.…”
Section: Ideas and Speculationmentioning
confidence: 99%
“…Different histone modifications furthermore regulate accessibility of the DNA leading to the less densely packed gene-rich euchromatin and the more densely packed transcriptional inactive heterochromatin (Y. Kim & Yu, 2020). Additionally, the chromatin fiber is folded by loop formation into topologically associated domains (TADs), which exhibit high self-interaction and bring far-distance regions of the genome into close proximity (Dixon et al,3 and higher cohesin stability when it is loaded at these sites, suggesting a loading mechanism primed by phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that cohesin extrudes loops in a two-sided manner [29,30]. Although theoretical considerations suggest, that two-sided LE by dimers of cohesin rings should take place in living mammalian cells [31], there are contradictory reports on whether this is actually the case in in vitro models [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This biological event is mediated by a ring-shaped complex cohesin which consists of four core components: SMC1, SMC3, SCC1 and SCC3 [10][11][12]. Besides sister chromatid cohesion and chromosome segregation, cohesin and its regulatory factors also exert functions in a variety of other biological processes such as DNA damage repair, transcriptional regulation and chromatin architecture organization [11][12][13][14][15]. Chromosome cohesion involves multiple steps including cohesin loading, cohesion establishment, cohesion maintenance and cohesion dissolution [11].…”
Section: Introductionmentioning
confidence: 99%